Delineating Hot Zone and Lineaments within Vredefort Crater in South Africa through Aeromagnetic Data Inversions - Muhammad B Atif; Yongzhi Wang; Muhammad P Akhter; Bello Y Ayoola; Lawal K Muideen; Fahad Hameed; Kateryna Hlyniana; Bo Wen; Zubair Nabi; Dong Yuhao; Yakubu M Bashir (Physics Access)
The Vredefort Dome has undergone some geologic processes that result in changes in the temperature of the rocks. This study contributes to the discussion on the thermal effect of the impact in the area on a regional scale and also delineates the linear structures around the Dome. The outcome shows that the center of the Dome is characterized by a low Curie point depth (CPD), indicating a high-temperature status that agrees with previous temperature reports in that area. The high-temperature tendency is observed to extend south of the Vredefort dome. The center-south of the Vredefort structure has a high thermal gradient and heat flow. The fractal distribution of the Vredefort structure correlates with the multi-ring structure around the Dome, which is peculiar to a few impact structures on Earth. The trend of the Fractal exponent contour around the center suggests that the contact of the meteoritic body at that region occurs at an angle and then pushes southwards. The structural analysis results show linear structures that are believed to be faults/fractures trending in North-NorthEast (NNE), NorthEast (NE), EastWest (EW), and NorthSouth (NS) directions whose effects have been explained in previous works in the area and were also identified on the ground. Some closures are observed at the center of the multi-ring structure, indicating the melt-dykes around the Vredefort dome. The Euler depth solutions cluster suggests the lineaments are about 7 km deep.